Rocky - Chartoff, Robert; Winkler, Irwin; Avildsen, John G., 1936-; Kirkwood, Gene.; Crabe, James; Stallone, Sylvester; Shire, Talia; Young, Burt.; Weathers, Carl.; Thayer, David, 1927-1978.; Spinell, Joe.; Gambina, Jimmy, 1943-; et al. ([Santa Monica, Calif.] : MGM, 2006)
Rocky Balboa, a club fighter seemingly going nowhere, gets his once-in-a-lifetime opportunity to go the distance and come out a winner when fate puts him in the ring with the world heavyweight champion.
Originally released as a motion picture in 1976.
Widescreen.
Music by Bill Conti ; art director, James H. Spencer ; edited by Richard Halsey ; executive in charge of production, Hal Polaire ; casting by Caro Jones ; production design by Bill Cassidy ; film editor, Scott Conrad ; looping editor, John Farrell ; boxing choreography, Sylvester Stallone ; costumer, Robert Cambel ; set decorator, Raymond Molyneaux.
Sylvester Stallone, Talia Shire, Burt Young, Carl Weathers, Thayer David, Joe Spinell, Jimmy Gambina, George Memmoli, Bill Baldwin, Billy Sands, Don Sherman, Shirley O'Hara, Tony Burton, Jodi Letizia, Burgess Meredith, guest appearance by Joe Frazier.
MPAA rating: PG.
DVD; English 5.1 DTS surround; English 5.1 Dolby Digital surround; English mono; French 5.1 Dolby Digital surround; Spanish mono.
Keywords: Boxers (Sports) -- Pennsylvania -- Philadelphia -- Drama; Boxing -- Drama; Man-woman relationships -- Drama; Feature films; Video recordings for the hearing impaired